The Analysis of Prepositional Phrases Found in Song Lyrics of Fool’s Garden’s Album Dish of the Day and Its Application in Teaching Writing Recount Text - Edy Prasetyo (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2019)
This study uses descriptive qualitative because the researcher would like todescribe about the structures and the function of prepositional phrases found in thesong lyrics of Fool’s Garden’s Album Dish of the Day and its application in teachingwriting recount text. The researcher used documentation method to collect the data.The researcher did some steps such as listening, searching, reading, finding, collectingdata and coding the data.The result of this study shows that there are three structures of prepositionalphrases. They are 96 Preposition + Noun / Noun Phrase (95. 5%), 4 Preposition + NounClause (3. 9 %), and 1 Preposition + ing Phrase (0. 9 %). Whereas, based on thefunctions, there are three functions of prepositional phrases. They are 17 post-modifierof a noun (20.4%), 5 post-modifier of an adjective (6.0%), and 61 adverbial (73.4 %). Inaddition, the prepositional phrases found in Song Lyrics of Fool’s Garden’s Album Dish ofthe Day can be applied in teaching writing at the tenth grade students of Senior HighSchool particularly in recount text.